Spider limb regeneration: Cost and benefits - Akamu Jude Ewunkem; Agee Kyle; Rivera Kayse (Global Journal of Zoology - Peertechz Publications, 2022)
One of the most phenomenal innate powers of organisms is their ability to repair injured or lost body parts better known as regeneration. Regeneration is the natural process of replacing or restoring missing body parts and is a primary attribute of all living organisms. Studying regeneration may be a potential for use in biomedical sciences. Closely associated with regeneration in the arthropods is autotomy an anti-predator behavior in animals. Autotomy is one of the most remarkable features of many arthropods, however, autotomy is not well known in spiders. Also, the cost and benefits of regeneration of lost limbs have not received much attention in recent decades. Understanding the cost-benefits dynamics of regeneration of lost limbs in spiders will undoubtedly increase our understanding of the evolutionary trajectory.  Spiders are remarkable for their ability to regenerate limbs with apparent ease during young stages. We used the huntsman spider Heteropoda venatoria as a model to address this. This mini-review also addresses the ecological implications of regeneration for spiders themselves. The study is of great importance because understanding the molecular mechanisms associated with regeneration could be exploited to reconstitute regeneration from constituent parts.